SKRINING FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK Padina australis DARI DESA SUMBERKIMA - Geeta Adsari Barus; I Nyoman Dodik Prasetia; Made Dwipa Kusuma Maharani; Gressty Sari Br Sitepu Sitepu (Universitas Mataram, 2026)
Padina australis is known to contain various bioactive compounds. This study examines the potential of Padina australis from Sumberkima Village, which has not been widely explored. The main objective of this research is to conduct phytochemical screening to identify the secondary metabolite profile and determine the level of antioxidant activity through the determination of the IC50 value, in order to provide a scientific data foundation for developing the potential of this seaweed, especially in the aquaculture sector. Sample extraction was performed using the maceration method with distilled water as the solvent and heating on a hot plate. The analyzed parameters were phytochemical content, which included quantitative tests for phenols, flavonoids, and tannins, and qualitative tests for saponins, alkaloids, and terpenoids, as well as antioxidant activity using the DPPH method. Data analysis was conducted descriptively to classify the strength of the antioxidant activity and the presence of phytochemical compounds. The quantitative phytochemical test results showed that the P. australis extract contained total phenols of 176.98 mg/100g, flavonoids of 101.49 mg/100g, and tannins of 5.31 mg/100g. Meanwhile, the qualitative tests showed negative results for saponins, alkaloids, and terpenoids. The antioxidant activity test results showed a very high IC50 value of 6213.2823 ppm, indicating that the antioxidant activity level of this extract is classified as very weak or inactive. This low antioxidant activity is suspected to be due to the combination of using distilled water as a solvent and an extraction method that is less effective in optimally extracting potent bioactive compounds. Therefore, further research with solvent variations or the application of modern extraction techniques is recommended.